THE INFLUENCE OF BRAND SIGNATURE, AWARENESS, ATTITUDE, AND REPUTATION ON PRIMEBIZ HOTEL SURABAYA’S BRAND PERFORMANCE - Setiawan, Andik; Sutarso, Yudi (Universitas Nahdlatul Ulama Surabaya, 2023)
Brand Performance has an important role for organizations to implement and improve good services and processes. This implies that management in the organization, must continuously improve the skills and ability to maintain and enhance the growth of the organization as well as to face the challenges of today's business. This study aims to examine the relationship between brand characteristics, brand attitude, brand reputation, brand awareness, and brand performance. This study used a quantitative approach with a data collection method using questionnaires on 111 primebiz hotel surabaya consumers and processed using partial least square (SmartPLS 3.0) analysis tools. The results showed that brand characteristics affect brand attitudes, brand attitudes affect brand reputation, brand characteristics affect brand awareness, brand awareness affects brand reputation, brand awareness affects brand attitudes and brand reputation affects brand performance.